Population Genomics of the Commercially Important Gulf of Mexico Pink Shrimp Farfantepenaeus duorarum (Burkenroad, 1939) Support Models of Juvenile Transport Around the Florida Peninsula - Timm, Laura E.; Jackson, Thomas L.; Browder, Joan A.; Bracken-Grissom, Heather D. (Frontiers in Ecology and Evolution, 2021)
The Gulf of Mexico pink shrimp, Farfantepenaeus duorarum, supports large fisheries in the United States and Mexico, with nearly 7,000 tons harvested from the region in 2016. Given the commercial importance of this species, management is critical: in 1997, the southern Gulf of Mexico pink shrimp fishery was declared collapsed and mitigation strategies went into effect, with recovery efforts lasting over a decade. Fisheries management can be informed and improved through a better understanding of how factors associated with early life history impact genetic diversity and population structure in the recruited population. Farfantepenaeus duorarum are short-lived, but highly fecund, and display high variability in recruitment patterns. To date, modeling the impacts of ecological, physical, and behavioral factors on juvenile settlement has focused on recruitment of larval individuals of F. duorarum to nursery grounds in Florida Bay. Here, we articulate testable hypotheses stemming from a recent model of larval transport and evaluate support for each with a population genomics approach, generating reduced representation library sequencing data for F. duorarum collected from seven regions around the Florida Peninsula. Our research represents the first and most molecular data-rich study of population structure in F. duorarum in the Gulf and reveals evidence of a differentiated population in the Dry Tortugas. Our approach largely validates a model of larval transport, allowing us to make management-informative inferences about the impacts of spawning location and recruitment patterns on intraspecific genetic diversity. Such inferences improve our understanding of the roles of non-genetic factors in generating and maintaining genetic diversity in a commercially important penaeid shrimp species.